A Wheat Cinnamyl Alcohol Dehydrogenase TaCAD12 Contributes to Host Resistance to the Sharp Eyespot Disease - Rong, Wei; Luo, Meiying; Shan, Tianlei; Wei, Xuening; Du, Lipu; Xu, Huijun; Zhang, Zengyan (Frontiers in Plant Science, 2016)
Sharp eyespot, caused mainly by the necrotrophic fungus Rhizoctonia cerealis, is a destructive disease in hexaploid wheat (Triticum aestivum L.). In Arabidopsis, certain cinnamyl alcohol dehydrogenases (CADs) have been implicated in monolignol biosynthesis and in defense response to bacterial pathogen infection. However, little is known about CADs in wheat defense responses to necrotrophic or soil-borne pathogens. In this study, we isolate a wheat CAD gene TaCAD12 in response to R. cerealis infection through microarray-based comparative transcriptomics, and study the enzyme activity and defense role of TaCAD12 in wheat. The transcriptional levels of TaCAD12 in sharp eyespot-resistant wheat lines were significantly higher compared with those in susceptible wheat lines. The sequence and phylogenetic analyses revealed that TaCAD12 belongs to IV group in CAD family. The biochemical assay proved that TaCAD12 protein is an authentic CAD enzyme and possesses catalytic efficiencies towards both coniferyl aldehyde and sinapyl aldehyde. Knock-down of TaCAD12 transcript significantly repressed resistance of the gene-silenced wheat plants to sharp eyespot caused by R. cerealis, whereas TaCAD12 overexpression markedly enhanced resistance of the transgenic wheat lines to sharp eyespot. Furthermore, certain defense genes (Defensin, PR10, PR17c, and Chitinase1) and monolignol biosynthesis-related genes (TaCAD1, TaCCR, and TaCOMT1) were up-regulated in the TaCAD12-overexpressing wheat plants but down-regulated in TaCAD12-silencing plants. These results suggest that TaCAD12 positively contributes to resistance against sharp eyespot through regulation of the expression of certain defense genes and monolignol biosynthesis-related genes in wheat.